2011
DOI: 10.1007/s11802-011-1800-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and salinity on germination of eelgrass (Zostera marina L.) seeds

Abstract: Seagrass restoration as part of ocean ecosystem protection has been launched for many years all over the world, but intensive research on this subject in China has just begun in recent years. Seed broadcasting has been widely accepted as the most potentially useful method for seagrass restoration over large areas. We examined the influence of key environmental factors on seed germination to help promote eelgrass bed restoration. Under anoxic conditions, the influence of temperature and salinity on the germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…Zhou et al (2015) reported that the shoot height of Z. marina from the Swanlake Lagoon was positively correlated with temperature. Similar to seagrass growth, seasonal fluctuations in temperature have been shown to control the germination of seagrass seeds from several species (Moore, Orth & Nowak, 1993; Walmsley & Davy, 1997; Probert & Brenchley, 1999; Pan et al, 2011a). It appears that the lowest seawater temperature of the local coastal area is related to the optimal seawater temperature for Z. marina seed germination (McMillan, 1983; Orth & Moore, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (2015) reported that the shoot height of Z. marina from the Swanlake Lagoon was positively correlated with temperature. Similar to seagrass growth, seasonal fluctuations in temperature have been shown to control the germination of seagrass seeds from several species (Moore, Orth & Nowak, 1993; Walmsley & Davy, 1997; Probert & Brenchley, 1999; Pan et al, 2011a). It appears that the lowest seawater temperature of the local coastal area is related to the optimal seawater temperature for Z. marina seed germination (McMillan, 1983; Orth & Moore, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for temperature effects on seagrass germination is equivocal, as some authors report enhanced germination rates with increasing temperature (e.g., Hootsmans et al, 1987;Jinhua et al, 2011;Kaldy et al, 2015), whereas others report no effects of temperature within the ranges explored (e.g., Phillips et al, 1983;Loques et al, 1990), even if some of these contrasting results refer to germination experiments conducted with the same species. These contrasting results reflect either local adaptation to particular spring regimes or the fact that the response of seagrass seed germination to temperature is likely to be best represented by a Gaussian distribution, with minimal and maximum thermal tolerances and an optimum temperature for germination.…”
Section: B2 Propagation Success: Climate Change Impacts On Early Lifementioning
confidence: 99%
“…Water depth and light attenuation may delay the duration and the timing of start and peak of flowering (Jacobs & Pierson 1981, Olesen et al 2017. Other local factors such as salinity may also affect germination success, with reduced salinity stimulating and advancing the emergence of seedlings (Phillips et al 1983a, Pan et al 2011. The timing of the end of the flowering season was, in particular, unrelated to latitude and temperature, suggesting that other drivers obscure the effect of climatic factors.…”
Section: Other Factors Potentially Influencing Eelgrass Phenologymentioning
confidence: 99%